Epidemiological profile of cutaneous Leishmaniasis in Brazil, 2015-2020 (Research, Society and Development, 2023)
Leishmaniasis is considered one of the most prevalent endemic diseases in the world (Pedrosa, 2007). Therefore, the present research focuses on the advance of tegumentary Leishmaniasis in the Brazilian territory. In view of this, an analysis of the epidemiological profile of the disease in Brazil by age group was carried out, the possible relationship between the prevalence of the disease and gender was verified and the comparison of the state of Rio Grande do Sul with the other Brazilian states, thus providing, a broad overview of the disease in the country. This is a quantitative, cross-sectional, descriptive study and used secondary data contained in the Health Information website (TABNET) of the Department of the Unified Health System (DATASUS). The highest incidence of cases of the disease is located in the North Region, it concentrates 46.31% of all cases. Right after it, is the Northeast Region with 24.73%, Midwest with 15.23%, Southeast Region with 12.09%, and finally, the South Region with 1.64% of cases. Regarding gender, the most affected were males (73%) and the age groups of 15-19 and 20-39 years were the ones that added the most cases of the disease. When comparing Brazil with the State of Rio Grande do Sul, it is noted that this state has the lowest rates of cases of tegumentary leishmaniasis in the country, about 5 cases per year